Investigating of Signal Propagation Characteristics in a Realistic Rural Scenario using Verified Tools: A Case of South Chunya-Tanzania - Yamakili, Pascal; Nicholaus, Mrindoko (AI Society & STMIK Indonesia, 2024)
Effective radio network planning requires understanding an area's radio propagation characteristics. This investigation uses dependable techniques to examine the movement of wireless signals in Tanzania's rural locations. Propagation characteristics in selected rural Tanzanian communities (South Chunya) are examined as a case study, and recommendations are made based on the findings, particularly for wireless service providers or researchers looking to improve wireless connectivity in rural communities. Important radio parameters such as Pathloss, Signal to Noise ratio, Bandwidth throughput, Spectral efficiency and Spectral band were examined. This was done after simulating signal transmission from the Base station transmitter to the Base station receiver and observing power and attenuation. Their corresponding results are discussed and evaluated. The general observation of the pass loss results for both operating frequencies 800MHz and 2000MHz have shown that only few areas are experiencing strong signal after initial signal power transmission, large areas served by these macro sites are experiencing huge path loss. This is evidently affected by the terrain of an area and the carrier frequency of operators.